Use of Oxygen at End-of-Life : Attitudes and Beliefs Survey - Mabin, Justin; Shaw, Timothy; Younger, Sarah (My University, 2013)
New scientific findings suggest that oxygen may not be necessary at end-of-life, and in fact, oxygen use may prolong death for those wanting to die. The purpose of this study was to survey health providers' opinions and experiences on the use of oxygen at the end of life.
Color poster with text, images, and tables.
Keywords: Terminal care--Decision making; Health care providers--Attitudes--Survey; Health care providers--Beliefs--Survey; Posters